DIfferences between men and women in the perception of partner’s authenticity - Grijak, Đurđa (Psihološka istraživanja, 2018)
The research was conducted to determine whether there were differences in the perception of partner’s authenticity depending on the respondents’ gender and age, the length of marriage, satisfaction with the relationship and satisfaction with the support of the partner. Respondents were 32 married couples (N=64), with the average age of 40 years. The length of marriage of the respondents ranged from 4 to 33 years. The Authenticity in Relationships Scale (Grijak, 2018) was used in the research.The results showed no statistically significant differences between men and women in the perception of partner’s authenticity. However, there were differences in the perception of partner’s authenticity with respect to the satisfaction with the relationship in men, as well as with respect to the age of women. The men who are more satisfied with the relationship with their partner and the women aged between 41 and 49 perceive their partners as more authentic.The presented research is a significant contribution to a more detailed interpersonal examination of authenticity and the goals of partners in a relationship.